Mapping the landscape of biology learning media publications in Indonesia: A bibliometric analysis - Dian Pratiwi; Sri Rahayu Lestari; Susriyati Mahanal (Journal of Research in Instructional, 2026)
Media integration in biology education is increasingly emphasized to support active, meaningful, and student-centered learning. This bibliometric analysis aims to explore trends, patterns, and research focus areas on media use in biology learning over the past ten years. This study employed a Scopus search using the keywords "Learning media" and "Biology," which then yielded 114 initial records. A PRISMA-based screening process was applied, limiting inclusion to original research articles published between 2016 and 2025, written in English, classified under the social sciences, and available as open access publications. After applying all criteria, 17 articles were included for in-depth analysis. The results show a fluctuating but generally increasing trend in publication frequency, especially in recent years. Most studies employed a research and development (RnD) method approach to evaluate the effectiveness of media in improving student learning outcomes and engagement. Indonesian authors contributed the most publications, with a high collaboration pattern of at least four authors on each published article. The biology topics studied include food biology, environmental biology, general biology, modern biology, genetics, biodiversity, botany, taxonomy, and immunology, all of which are topics with high conceptual complexity and therefore require the support of visual and interactive media in their learning. This review successfully maps the research landscape on the use of media in biology education and serves as a valuable reference for future studies in selecting relevant biological content, methodological frameworks, and collaborative approaches.